More than a Ban on Smoking? Behavioural Spillovers of Smoking Bans in the Workplace - Joan Costa-i-Font; Luca Salmasi; Sarah Zaccagni (Center for Economic Studies and ifo Institute (CESifo), 2022)
Are workplace smoking bans (WSBs) more than a ban on smoking? We study whether WSBs influence smoking cessation and exert behavioural spillover effects on (i) a set of health behaviours, and (ii) on individuals not directly affected by the bans. Drawing upon quasi-experimental evidence from Russia, which introduced a WSB (in addition to a ban on smoking in public places), and adopting a difference-in-differences (DiD) strategy, which compares employed individuals (exposed to the work and public place ban) to unemployed individuals (exposed only to the ban in public places), we document three sets of findings. First, unlike previous studies that focus on smoking bans in public places, we find robust evidence that WSBs increase smoking cessation by 2.9 percentage points (pp) among men. Second, we find that quitters are less likely to use alcohol (6.7 pp reduction among men and 3.5 pp among women), and they reduce their alcohol consumption (10 percent among men). WSBs are found to influence the health behaviour of those not directly affected by the reform, such as never smokers. Our findings are consistent with a model of joint formation of health behaviours, and suggest the need to account for a wider set of spillover effects when estimating the welfare effect of WSBs.
Keywords: I18; H75; L51; 330; joint formation of behaviours; workplace smoking bans; behavioural spillovers; smoking; drinking; physical activity; healthy identity; Russia